Isotermal Adsorpsi Ion Tembaga (II) Menggunakan Arang Tongkol Jagung (Zea mays L.) Teraktivasi Kalium Permanganat: Isothermal Adsorption of Copper (II) Ions Using Charcoal from Corn Cobs (Zea mays L.) Activated by Potassium Permanganate - Lisma Habiba; Nov Irmawati Inda; Prismawiryanti; Husain Sosidi; Ni Ketut Sumarni; Dwi Juli Puspitasari; Moh. Mirzan; Jusman (KOVALEN: Jurnal Riset Kimia, 2023)
Corn cobs which generally only become waste can be processed into activated carbon and used for the absorption of heavy metals, such as copper(II) ions. This study aims to determine the morphology of corn cobs charcoal after activation, determine the isothermal adsorption model of copper (II) metal ions on corncob-activated carbon, and then determine the adsorption capacity of copper (II) metal ions on corncob-activated carbon. The morphology of the corncob-activated charcoal obtained was analyzed using Scanning Electron Microscopy (SEM). Isothermal adsorption of copper (II) ions was carried out with various concentrations of copper (II) ions of 5, 10, 20, 50, and 100 ppm. The results of the analysis using SEM showed that the surface shape of the corncob-activated charcoal is regular and has pores with a pore diameter obtained in the range between 1.08-1.26 m and 1.38-1.59 m. The mechanism of adsorption of copper (II) ions by corncob-activated charcoal using KMnO4, following the Freundlich isothermal model with a value of R2 0.9993 with an adsorption capacity of 51 x 10-4 mmol/L. The utilization of activated carbon from corn cobs that are activated by potassium permanganate is very effective for adsorbing copper metal ion pollutants through an adsorption mechanism on the surface of activated carbon.